The Theological Meaning of Al-Hamdalah - Obaid, Hasan; Shareef, Raad (Jordan Journal of Islamic Studies, 2023)
The research aims to convey the interdependence between dhikr and faith, for the speech and the theological meaning between them, is profound. It has a close relationship, especially in Al-Hamdallah, which is the core of this article. And with its remembrance, the balance is filled. So how? And what does it mean? Why is it the opening of the greatest surah in the Qur'an and even other surahs? When does a believer reach the highest level in the scale of praisers? The abundance of meanings and the relationships of praise with other related words has turned the research to reveal the darkness of ignorance among Muslims who stood at the word without thinking its connotations and purposes. The research terms give the keys to understanding praise and other dhikrs. It includes five demands: the first is the linguistic and idiomatic meaning of praise, the second is the difference between praise, appreciation, thanksgiving, and advocacy, the third in the sections of praise and the types of praisers, and the fourth includes faith conclusions and the fifth clarifies the relationship of praise with the names of God, such as Al-Hamid, and Al-Shakur.